2020
DOI: 10.1001/jamanetworkopen.2020.4099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Detection of Elder Mistreatment Through Emergency Care Technicians Project Screening Tool

Abstract: IMPORTANCEElder mistreatment is underdetected and underreported. The more than 800 000 medics providing services in every county in the United States represent an important and underused surveillance system. OBJECTIVE To investigate the association between the Detection of Elder Mistreatment Through Emergency Care Technician (DETECT) screening tool use and the number of medic reports made to Adult Protective Services (APS) over a period of approximately 3 years. DESIGN, SETTING, AND PARTICIPANTS This quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Nineteen articles focused on the development and evaluation of screening tools. Eleven tools were discussed including tools designed specifically for medical providers: (1) TEAM-FACN (Burnett et al, 2019), (2) detection of elder abuse through car emergency care technician (DETECT) (Cannell et al, 2019; Cannell, Livingston, et al, 2020; Cannell, Weitlauf, et al, 2020), (3) QualCare Scale ( et al, 2017) and social workers: (4) EARAE tool (Dauenhauer et al, 2019), (5) OAFEM tool (Phelan et al, 2017), and the (6) Emergency Department Elder Mistreatment Assessment Tool for Social Workers (Elman et al, 2020). The other five tools were designed for use by all professionals: (7) indicators of abuse Screen instrument (Touza et al, 2018), (8) the caregiver abuse screen tool (Pérez-Rojo et al, 2015; Sakar et al, 2019, (9) the Weinberg center risk and abuse prevention screen (Ramirez et al, 2019), (10) risk on elder abuse and mistreatment instrument (De Donder et al, 2018), and (11) Australian elder abuse screening instrument (Gahan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen articles focused on the development and evaluation of screening tools. Eleven tools were discussed including tools designed specifically for medical providers: (1) TEAM-FACN (Burnett et al, 2019), (2) detection of elder abuse through car emergency care technician (DETECT) (Cannell et al, 2019; Cannell, Livingston, et al, 2020; Cannell, Weitlauf, et al, 2020), (3) QualCare Scale ( et al, 2017) and social workers: (4) EARAE tool (Dauenhauer et al, 2019), (5) OAFEM tool (Phelan et al, 2017), and the (6) Emergency Department Elder Mistreatment Assessment Tool for Social Workers (Elman et al, 2020). The other five tools were designed for use by all professionals: (7) indicators of abuse Screen instrument (Touza et al, 2018), (8) the caregiver abuse screen tool (Pérez-Rojo et al, 2015; Sakar et al, 2019, (9) the Weinberg center risk and abuse prevention screen (Ramirez et al, 2019), (10) risk on elder abuse and mistreatment instrument (De Donder et al, 2018), and (11) Australian elder abuse screening instrument (Gahan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The team first identified the most salient indicators of elder abuse and neglect for potential inclusion on a screening tool (Cannell et al, 2016). They went on to evaluate the general effectiveness of the tool (Cannell, Livingston, et al, 2020), feasibility of implementing DETECT into medic’s field-based practice (Cannell et al, 2019), and the validity of an abbreviated version of the tool (Cannell, Weitlauf, et al, 2020). Overall, they found that the DETECT tool was effective in increasing emergency medics’ frequency of reporting.…”
Section: Resultsmentioning
confidence: 99%
“…If there is concern for intentional abuse or neglect, Adult Protective Services or a long‐term care ombudsman should be alerted by ED staff. Integration of a vulnerable elder team or validated screening tool for elder mistreatment increases identification and assists with getting services for these patients 105,106 . The transition of care to home and assessment of caregiver burden or elder mistreatment are very important areas of emergency care where the involvement of experienced social work, case management, and rehabilitation teams are critical.…”
Section: Transition Of Carementioning
confidence: 99%
“…It includes a brief prescreen intended for all patients followed by a longer comprehensive screen for those with positive responses on the prescreen. It also includes prompted older adult and caregiver observations derived from the DETECT screening tool, validated to detect EA in the field by emergency responders, 23 as well as physical examination components and suggested response pathways following assessment. In a multicenter validation study, the original EA screening tool on which EM‐SART is based, the ED Senior AID Tool, had a sensitivity of 94.1% and specificity of 84.3% for identifying EA cases confirmed by multidisciplinary expert panel review and the approach was found to be acceptable to ED providers 22 …”
Section: Introductionmentioning
confidence: 99%